2018
DOI: 10.1242/dev.164723
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor SOX30 is a key regulator of mouse spermiogenesis

Abstract: The postmeiotic development of male germ cells, also known as spermiogenesis, features the coordinated expression of a large number of spermatid-specific genes. However, only a limited number of key transcription factors have been identified and the underlying regulatory mechanisms remain largely unknown. Here, we report that SOX30, the most-divergent member of the Sry-related high-motility group box (SOX) family of transcription factors, is essential for mouse spermiogenesis. The SOX30 protein was predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 63 publications
6
29
3
Order By: Relevance
“…Sox30 is a member of the Sox transcription factor family and exists in many animals, including teleosts and mammals [2,9,30]. It has been demonstrated in mouse that the Sox30 gene is predominantly expressed in testis and Sox30 knockout results in an abnormal spermiogenesis [7,8]. In the present study, we observed in Nile tilapia that the Sox30 gene is expressed in epithelial cells of the intratesticular efferent duct of the testis.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Sox30 is a member of the Sox transcription factor family and exists in many animals, including teleosts and mammals [2,9,30]. It has been demonstrated in mouse that the Sox30 gene is predominantly expressed in testis and Sox30 knockout results in an abnormal spermiogenesis [7,8]. In the present study, we observed in Nile tilapia that the Sox30 gene is expressed in epithelial cells of the intratesticular efferent duct of the testis.…”
Section: Discussionsupporting
confidence: 51%
“…Sox30 is the only member of group H of the Sox family and exists widely among the animal kingdom [2,3,4,5], including human ( Homo sapiens ), mouse ( Mus musculus ), chicken ( Gallus gallus ), Nile tilapia, the channel catfish ( Ictalurus punctatus ), guppy ( Poecilia reticulata ), fathead minnow ( Pimephales promelas ), little skate ( Leucoraja erinacea ), dogfish ( Squalus acanthias ), lancelets ( Branchiotoma belcheri ), and elephant shark ( Callorhinchus milii ). Although the roles of the Sox30 protein in teleost are currently unclear, recent studies in mouse have demonstrated that Sox30 is involved in spermiogenesis and Sox30 knockout results in abnormality in germ cell development and a complete arrest of spermiogenesis [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SOX30 protein (SRY-box containing gene 30), the only member of group H, has been characterized briefly only in a few species so far. SOX30 has been isolated from mice, humans and Nile tilapis, and it has been connected with mammalian spermatogonial differentiation and spermatogenesis [69][70][71][72]. Recently, it has been demonstrated that the SOX30 protein could be a novel epigenetic silenced tumor suppressor that acts through the direct regulation of p53 in human lung cancer [73,74].…”
Section: Sox Protein Familymentioning
confidence: 99%